Neonatal gastrointestinal involvement and congenital cytomegalovirus - Alessandro Porta; Adriana Avanzini; Marta Bellini; Rosa Maria Crossignani; Stefano Fiocchi; Stefano Martinelli; Luciana Parola (PAGEPress Publications, 2016)
Cytomegalovirus (CMV) is the most common cause of congenital viral infection, affecting 0.2 to 2.3% of all live births in developed countries. Very low birth weight and extremely low birth weight newborns are at higher risk of symptomatic CMV infection, most commonly secondary and acquired through breast milk. Gastrointestinal involvement is rare in acquired CMV infections, but it could be an important manifestation of postnatal infection in preterm infants admitted to neonatal intensive care units. Early onset of CMV gastrointestinal signs/symptoms is very rare. In a review of the literature it is described in 5 newborns in the first 24 hours of life, and 6 considering the onset in the first week of life. This review describes also a case report of congenital CMV in an immunocompetent newborn with onset of gastrointestinal signs immediately after birth: a possible association between viral infection and enteric manifestations was considered in the differential diagnosis. A review of the literature of the different case reports found has done, with description and comparison of the different patients and clinical presentations.